Bioenergy harvest, climate change, and forest carbon in the Oregon Coast Range. Issue 2 (25th May 2015) - Creutzburg, Megan K.; Scheller, Robert M.; Lucash, Melissa S.; Evers, Louisa B.; LeDuc, Stephen D.; Johnson, Mark G.
Abstract: Forests provide important ecological, economic, and social services, and recent interest has emerged in the potential for using residue from timber harvest as a source of renewable woody bioenergy. The long‐term consequences of such intensive harvest are unclear, particularly as forests face novel climatic conditions over the next century. We used a simulation model to project the long‐term effects of management and climate change on above‐ and belowground forest carbon storage in a watershed in northwestern Oregon. The multi‐ownership watershed has a diverse range of current management practices, including little‐to‐no harvesting on federal lands, short‐rotation clear‐cutting on industrial land, and a mix of practices on private nonindustrial land. We simulated multiple management scenarios, varying the rate and intensity of harvest, combined with projections of climate change. Our simulations project a wide range of total ecosystem carbon storage with varying harvest rate, ranging from a 45% increase to a 16% decrease in carbon compared to current levels. Increasing the intensity of harvest for bioenergy caused a 2–3% decrease in ecosystem carbon relative to conventional harvest practices. Soil carbon was relatively insensitive to harvest rotation and intensity, and accumulated slowly regardless of harvest regime. Climate change reduced carbon accumulation in soil and detrital pools due to increasing heterotrophic respiration, and had small but variable effects on aboveground live carbon and total ecosystem carbon. Overall, we conclude that current levels of ecosystem carbon storage are maintained in part due to substantial portions of the landscape (federal and some private lands) remaining unharvested or lightly managed. Increasing the intensity of harvest for bioenergy on currently harvested land, however, led to a relatively small reduction in the ability of forests to store carbon. Climate change is unlikely to substantially alter carbon storage in these forests, absent shifts in disturbance regimes.